The Severity and Extent of Coronary Artery Disease in Khat User Yemeni Patients - A. S. MD, Al-Zendani; B. A., MD., Al-Dobhani; H. M., MD, Al-Garmozi; Al-Zaazaai, M.Sc., Ali Ahmed (International Journal of Innovative Research in Medical Science, 2020)
Background: Khat is the leaves of the Catha Edulis plant, contains cathinone, ephedrine, epinephrine, and other substances. Khat chewing is one of the major social habits in Yemen and some studies reported that the khat chewing is associated with worse outcome in patients with acute coronary syndrome compared with non-khat users but there are limited data about the effect of khat and the severity of coronary artery disease. Objectives: This study was performed to determine the extent and severity of coronary artery disease in khat chewer patients in Yemen. Patients and Method: Patients who underwent coronary angiography as a planned procedure at the cardiac center of Al-Thawra Modern General Hospital over six months duration were included in this cross-sectional prospective study. A well-designed questionnaire was filled which including complete personal and clinical history for each patient, the presence of CHD risk factors, echocardiography, and coronary angiography findings. The data after that were analyzed using the SPSS program and different correlations were statistically established among variables. Results: The total number of patients admitted with a diagnosis of ischemic heart disease and planned for coronary angiography were 365 patients in which khat chewer patients group were 306 (84%) compared with 59 (16%) of non-khat chewers. The mean ages were (55+ -10 vs. 57+ -9, P=0.396). History of smoking was (83% vs. 17%, P<0.001) in khat chewers and non-khat chewers respectively. The prevalence of DM & HTN were (44% vs. 36%, P=0.243) & (30% VS. 39%, P=0.I194) in comparing both groups respectively. The history of the acute coronary syndrome was more prevalent among the khat chewer patients group (54% vs. 24%, P<0.001). Impaired LV systolic function was more prevalent among khat chewer patients group associated with a significant statistical difference & EF<50% was(39% vs. 23%, P=0.024) in both groups respectively. The significant coronary stenosis was more frequent in the khat chewer patients group (66% vs. 45%, P=0.O42). The khat chewer patients group also had more atherosclerotic coronary arteries (64% vs. 50%, P=0.056), more prevalence of multi-vessel disease (27% vs. 22%, P=0.090), and more frequent of type C coronary artery lesions complexity (20% vs. 12%, P=0.011). On the other hand, the history of recurrent stable angina was more prevalent among the non-khat chewer patients group (76% vs. 45%, P<0.001) & the normal coronary arteries were more frequent among the non-khat chewer patients group (46% vs. 29%, P<0.001). Conclusion: Khat chewer patients had more atherosclerotic coronary arteries, more lesion complexity, a severe form of coronary artery disease, and more prevalence of the multi-vessel disease. Finally, we concluded that khat chewing is one of the risk factors of coronary artery disease in Yemen.